Tuning the Consonance of Microscopic Neuro-Cardiac Interactions Allows the Heart Beats to Play Countless Genres - Franzoso, Mauro; Dokshokova, Lolita; Vitiello, Libero; Zaglia, Tania; Mongillo, Marco (Frontiers in Physiology, 2022)
Different from skeletal muscle, the heart autonomously generates rhythmic contraction independently from neuronal inputs. However, speed and strength of the heartbeats are continuously modulated by environmental, physical or emotional inputs, delivered by cardiac innervating sympathetic neurons (cSNs), which tune cardiomyocyte (CM) function, through activation of beta-adrenoceptors (beta-ARs). Given the centrality of such mechanism in heart regulation, beta-AR signaling has been subject of intense research, which has reconciled the molecular details of the transduction pathway and the fine architecture of cAMP signaling in subcellular nanodomains, with its final effects on CM function. The importance of mechanisms keeping the elements of beta-AR/cAMP signaling in good order emerges in pathology, when the loss of proper organization of the transduction pathway leads to detuned beta-AR/cAMP signaling, with detrimental consequences on CM function. Despite the compelling advancements in decoding cardiac beta-AR/cAMP signaling, most discoveries on the subject were obtained in isolated cells, somehow neglecting that complexity may encompass the means in which receptors are activated in the intact heart. Here, we outline a set of data indicating that, in the context of the whole myocardium, the heart orchestra (CMs) is directed by a closely interacting and continuously attentive conductor, represented by SNs. After a roundup of literature on CM cAMP regulation, we focus on the unexpected complexity and roles of cardiac sympathetic innervation, and present the recently discovered Neuro-Cardiac Junction, as the election site of ‘SN-CM’ interaction. We further discuss how neuro-cardiac communication is based on the combination of extra- and intra-cellular signaling micro/nano-domains, implicating neuronal neurotransmitter exocytosis, beta-ARs and elements of cAMP homeostasis in CMs, and speculate on how their dysregulation may reflect on dysfunctional neurogenic control of the heart in pathology.